Occult and manifest colorectal carcinoma in ulcerative colitis: how does it influence surgical decision making? - Hardt, Julia; Kienle, Peter (Visceral medicine, 2015)
Background: The incidence of colorectal cancer (CRC) among patients with ulcerative colitis (UC) is increased compared to the general population. The diagnosis of CRC potentially influences surgical decision making in patients with UC. Methods: This review considers clinical studies, systematic reviews, and guidelines on the surgical therapy of CRC in UC. We searched the bibliographic databases The Cochrane Library and Medline (applying MeSH terms such as ‘Colitis, Ulcerative/surgery', ‘Colorectal Neoplasms', and ‘Proctocolectomy, Restorative') with no restriction on language, date, or country. Search results as well as references of relevant publications were independently screened by both authors of this review. Results: The surgical gold standard for proven CRC in UC is oncological proctocolectomy, if possible preferably as a restorative procedure with formation of an ileal pouch-anal anastomosis. Mucosectomy and hand-sewn anastomosis is the preferred option for fashioning the anastomosis in these patients, especially in case of dysplasia or cancer in the rectum, although the available data is not conclusive. In highly selected cases of patients with histologically confirmed sporadic CRC without dysplasia in multiple random biopsies and without relevant inflammation, a conventional limited oncological resection is adequate. If UC patients with rectal cancer require radiotherapy, it should be performed in a neoadjuvant setting because of the high risk of radiation-induced pouch failure. Conclusion: Although restorative proctocolectomy is clearly the gold standard therapy for patients with CRC in UC, surgical decision making has to take into account the various settings and patient factors.
Gesehen am 03.12.2018